Feasibility and Potential Effectiveness of a Smartphone Zero-Time Exercise Intervention for Promoting Physical Activity and Fitness in Patients With Coronary Heart Disease: A Pilot Randomized Controlled Trial - Noel P. T. Chan; Noel P. T. Chan; Agnes Y. K. Lai; Hau K. Choy; Derek Y. T. Cheung; Alice N. T. Wan; Alice N. T. Wan; Victor Y. H. Cheng; Ka Y. Chan; Yuk K. Lau; Chi Y. Yung; George O. C. Cheung; et al. (Frontiers Media S.A., 2022)
BackgroundZero-time Exercise (ZTEx), a simple strength- and stamina-enhancing physical activity (PA) requiring no extra equipment, can potentially increase PA and fitness. This pilot trial examined the feasibility and potential effectiveness of a smartphone ZTEx intervention to promote PA and fitness in patients with coronary heart disease (CHD).MethodsA parallel-group assessor-blinded pilot randomized controlled trial was conducted on Chinese patients with stable coronary heart disease (CHD) in three cardiology clinics. The experimental group received a 15-min brief individual face-to-face session and a 12-week ZTEx instant messaging with 28 picture e-messages and a smartphone ZTEx application (ZTExApp). The control group received the same duration of individual session and number and format of e-messages, but the content was healthy eating and breathing exercise. The feasibility was assessed based on: attrition rate, usage, response rate and perception of the intervention. The outcome evaluation included primary outcome (PA), fitness, exercise self-efficacy and intention, perceived happiness and health, and quality of life. A linear mixed model was used with intention-to-treat analysis adjusting for sex, age and baseline values. A semi-structured interview was conducted to collect feedback from the experiment group.ResultsOne hundred thirty-nine patients (mean age 59.8 ± 6.6; 71.2% male) were randomized to the experimental group (n = 70) or control group (n = 69), and 80% (56/70) and 82% (57/69) of patients completed the 12-week follow-up assessment, respectively. The attrition rate was 18.7%. The experimental group reported that ZTEx was feasible to integrate PA into their daily life and appreciated the picture e-messages, and 95% of them sent feedback to us, but only 19.6% (13/70) of the participants entered their PA information into the e-diary of the ZTExApp. The experimental group had a significantly greater increase in time spent walking [mean difference (95% CI): 155.3 (10.1, 300.4), P = 0.04, Cohen's d = 0.34] than the control group.ConclusionsThis pilot study showed using a brief ZTEx face-to-face session with picture e-messages empowered patients with CHD to integrate PA into daily life. Future definitive trials with a longer follow-up and a more user-friendly ZTExApp interface are necessary to determine the effectiveness of the smartphone ZTEx intervention in enhancing PA and related outcomes.Trial RegistrationThe research protocol was registered at the Hong Kong University Clinical Trials Registry (HKUCTR) on 22 Jul 2016 (Study identifier: HKUCTR-2165) and was also retrospectively registered at the National Institutes of Health (identifier number: NCT03464331) on 14 March 2018.